The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/978-3-658-28681-1
|View full text |Cite
|
Sign up to set email alerts
|

Selbstreguliertes Lernen im Mathematikstudium

Abstract: Die Deutsche Nationalbibliothek verzeichnet diese Publikation in der Deutschen Nationalbibliografie; detaillierte bibliografische Daten sind im Internet über http://dnb.d-nb.de abrufbar.Springer Spektrum © Springer Fachmedien Wiesbaden GmbH, ein Teil von Springer Nature 2020 Das Werk einschließlich aller seiner Teile ist urheberrechtlich geschützt. Jede Verwertung, die nicht ausdrücklich vom Urheberrechtsgesetz zugelassen ist, bedarf der vorherigen Zustimmung des Verlags. Das gilt insbesondere für Vervielfälti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Interestingly, a differentiated analysis shows that beyond the achievement in the preliminary test, participation in tutorials seems to have a stronger impact on students' achievement in final exams than in the students' achievement in the tutorials. We interpret this finding as a result of students' tendency to copy homework, which is the basis for achievement in tutorials, instead of paying attention during tutorials (Göller 2020).…”
Section: Relationships Among Theoretical Constructsmentioning
confidence: 88%
See 1 more Smart Citation
“…Interestingly, a differentiated analysis shows that beyond the achievement in the preliminary test, participation in tutorials seems to have a stronger impact on students' achievement in final exams than in the students' achievement in the tutorials. We interpret this finding as a result of students' tendency to copy homework, which is the basis for achievement in tutorials, instead of paying attention during tutorials (Göller 2020).…”
Section: Relationships Among Theoretical Constructsmentioning
confidence: 88%
“…5 Data collection during the first year of engineering studies; the first final exam is on linear algebra, the second exam to analysis exam. Finally, research has shown that students tend to copy homework instead of solving the tasks for themselves (Göller 2020). For this reason, the results concerning achievement in homework have to be carefully interpreted.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, also concerning students' review of mathematics lectures, problems are documented in the literature. Students often focus their work out of class on homework problems they are required to solve (Göller, 2019). In advanced mathematics courses these problems often have the purpose of elaborating students' understanding of the mathematical theory covered in the lecture, and already require an initial grasp of the concepts, theorems, and proofs presented there (Bauer, 2015).…”
Section: Students' Difficulties In Learning From Mathematics Lecturesmentioning
confidence: 99%
“…Finally, the approach could also address problems concerning students' post-class processing of mathematics lectures. If students already gain an understanding of the formal lecture content in class, an intensive post-class processing is no longer necessary, which can address the problem that students often do not post-class process mathematics lectures intensively (Bauer, 2015;Göller, 2019). Furthermore, the instructor's in-class activities illustrating how experts in mathematics make sense of the definitions, theorems, and proofs covered could provide students with meta-knowledge of how they could post-class process a traditional advanced mathematics lecture, which remains often implicit.…”
Section: Potentialities Of the Flipped Classroom In This Adaptation To Address Students' Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation